Considering risk, responsibility, and reward: the experiences of women of color in science speaking truth to power - Moreira, Stephanie "Mo", author; Basile, Vincent, advisor; Archibeque-Engle, Shannon, committee member; Diaz, Hermen, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2023)
The purpose of this study was to understand the risks, responsibility, and rewards women of color in the sciences navigate and negotiate when choosing to speak truth to power. The theoretical lenses that guided this work included Critical Race Theory, Critical Feminist Theory, Harding's strong objectivity, and Foucault's analysis of parrhesia (speaking truth to power). Employing the counternarrative, participants were provided an opportunity to reflect on their intentions, motivations, and behaviors when choosing to be outspoken about oppression in their personal and professional settings. The research questions for this study were: (1) What motivating factors guide women of color in the sciences to choose to speak truth to power? (2) How do women of color in the sciences envision the future of science culture? If speaking truth to power is a game, as Foucault suggests, the study identified five rules that served as a social contract for women of color in science. The emerging rules include: (1) stay true to oneself, (2) avoid ruining it for other women of color, (3) live to die another day, (4) if you must leave, go out on your own terms, and (5) share the map with others. Manipulating relationships and creating boundaries served as strategies that women of color in science uniquely operationalize to achieve their goals.
Keywords: science; STEM; women of color; speaking truth to power; activism; students of color